O território usado e a saúde nas cidades pequenas: um estudo de caso sobre o Departamento Regional de Saúde de Sorocaba entre 2008 e 2018 - Pinto, Ronaldo Ramos (2023)
Health has always been an extremely researched topic in various fields of knowledge. Among them, Geography of Health has sought to work on the relationship of health with the environment. This research follows the same line, as it sought to understand the distribution of hospitals by place of residence in the small towns of the Regional Department of Health of Sorocaba (DRS) and to compare them with the territory uses existing in these cities. The work was based mainly on the concept of territory used. In the analysis of the 35 small cities that fall within the present proposal, it was found that those included in the Sorocaba Metropolitan Region have greater influence on the industrial dynamics and have lower rates of internment. By contrast, cities that are not in the metropolitan dynamics have been characterized by a dynamic of the uses of the territory focused on the area of services and in the field of agricultural production and lead the ranking in the number of hospitals.